2019
DOI: 10.3390/polym11030457
|View full text |Cite
|
Sign up to set email alerts
|

Alginate/Gelatin Hydrogels Reinforced with TiO2 and β-TCP Fabricated by Microextrusion-based Printing for Tissue Regeneration

Abstract: Three-dimensional (3D) printing technologies have become an attractive manufacturing process to fabricate scaffolds in tissue engineering. Recent research has focused on the fabrication of alginate complex shaped structures that closely mimic biological organs or tissues. Alginates can be effectively manufactured into porous three-dimensional networks for tissue engineering applications. However, the structure, mechanical properties, and shape fidelity of 3D-printed alginate hydrogels used for preparing tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…Concentrated alginate/gelatin scaffolds with homogeneous nano-apatite coating were fabricated by 3D printing followed by in situ mineralization for application in bone tissue engineering [112]. In addition, alginate/gelatin constructs reinforced with TiO 2 and β-tricalcium phosphate fabricated by micro-extrusion-based printing showed enhanced mechanical properties up to 20 MPa of elastic modulus [113].…”
Section: Various Forms Of Scaffolds Based On Gumsmentioning
confidence: 99%
“…Concentrated alginate/gelatin scaffolds with homogeneous nano-apatite coating were fabricated by 3D printing followed by in situ mineralization for application in bone tissue engineering [112]. In addition, alginate/gelatin constructs reinforced with TiO 2 and β-tricalcium phosphate fabricated by micro-extrusion-based printing showed enhanced mechanical properties up to 20 MPa of elastic modulus [113].…”
Section: Various Forms Of Scaffolds Based On Gumsmentioning
confidence: 99%
“…In addition, to improve mechanical stability, multi-nozzle systems have been used to simultaneously print a support structure made of PCL alongside alginate hydrogel structures [250,251]. Other ways to improve the mechanical stability after print are by formulation of alginate ink mixed with PVA powder (printability decreased and compressive modulus decreased from 56 to 13 kPa with increasing PVA content from 0 to 30% v/v [252]), or TiO 2 (Young's modulus of 13 MPa compared with control of 9 MPa), or β-TCP (Young's modulus of 8 MPa) [253]. For light-assisted fabrication, methacrylated alginate hydrogels have been photopolymerized with UV light allowing tunable swelling and mechanical properties [254].…”
Section: Structural and Mechanical Propertiesmentioning
confidence: 99%
“…Inclusion of NiCu [237], e-polylysine [238], carrageenan [239], gelatin [240][241][242], cellulose [243,244], PVA [252], TiO 2 [253], β-TCP [253]; Feature size 150 µm, E: 280 kPa [240] Myoblasts [242]; endothelial cells [259]; E.coli [260], growth factor [250], human adipose stem cells [248]; human induced pluripotent stem cells [261]; chondrocytes [243,244,251]; Schwann cells [265] Cellulose (4.3.4) Mixed with alginate [244,[266][267][268][269][270][271][272]; As reinforcement material, E: 2.5-22.5 kPa [281] Feature size 500 µm [280]; Tensile E: 0.67-0.63 GPa [282] Chondrocytes for cartilage tissue engineering [244,269,271]; human induced pluripotent stem cells, bone-marrow hMSCs [272]; pancreatic cancer cells [268]; fibroblast and hepatoma cells [270]; NIH 3T3 cells [274] Collagen (4.4.1)…”
Section: ) Applicationsmentioning
confidence: 99%
“…These synthetic routes are effective to fabricate polysaccharide-hybrid structures with enhanced technological properties and applications [3]. Currently, there is a special interest in combining organic compounds such as polysaccharides with inorganic compounds like titanium dioxide (TiO 2 ) to obtain hybrid materials with enhanced stability and new functionalities [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the use of TiO 2 as a reinforcement agent of polysaccharide-based materials has been explored [5,11,20]. Teymourpour et al [6] reported that the soybean polysaccharide biocomposite reinforced with TiO 2 showed good antimicrobial activity against Escherichia coli and Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%